Auditoría de gestión y su relación con el desarrollo de la empresa comercial Tecnoplanet, cantón Quevedo, período 2012 - Vera Cedeño, José Mauricio (2015)
This research was carried out in the TECNOPLANET trading company, Quevedo Canton Street Jose Joaquin de Olmedo and Colombia in the above a performance audit and its relationship with the progress of Tecnoplanet trading company during the period 2012, was developed for this study basic office supplies and equipment used also historical, analytical, scientific methods inductive - deductive regarding the types of research the film, exploratory, descriptive and field sample was also established in 178 was handled after applying the Formula n = N / (E ^ 2 (N-1) +1) .In obedience to the specific objectives was just this evaluation checking the level that keeps the company in the internal control processes then apply the model of Internal Control COSSO I managed to prove that the company has a moderate level of confidence equivalent to 66% and 34% risk is considered high by this model could detect the findings as shortage of policy and regulations, lack of management indicators also not fully carried out the procedure for the correct process of shopping, internet facilities do not comply with proper procedure. In the assessment that was made to the company's customer satisfaction it was determined by 67% and the management was established with an efficiency of 99% and 98% efficiency, allowing draw recommendations for greater efficiency and effectiveness. The development of a management audit report enabling the company Tecnoplanet optimizing their resources. In the assessment made by the company is recommended to implement the necessary controls that allows for a higher level of confidence, also it suggests that the company improve controls in relation to what is the efficiency and effectiveness and to establish a system of measurement indicators management.